2022
DOI: 10.6000/1929-4409.2020.09.270
|View full text |Cite
|
Sign up to set email alerts
|

Principles Behind Semantic Relation between Common Abbreviations and their Expansions on Instagram

Munirah Hasjim,
Burhanuddin Arafah,
Kaharuddin
et al.

Abstract: The phenomenon of abbreviation used on Instagram is an interesting thing since the users modify the abbreviation form of expansion words making deviation from the original meaning. The principle of meaning relation between abbreviations and their expansions is used to make a change to the purposes of Instagram users. This research was aimed to describe the principle of abbreviation used in Instagram. An exploitation method was used by the technique of making screenshots and recording the abbreviation data. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…This shows a deep understanding of the concept of using technology. Teachers should be able to communicate effectively, using clear and comprehensible language to positively influence students' perceptions (Yulianti et al, 2022;Hasjim et al, 2020;. It is an attempt to avoid multiple interpretations of using difficult dictions and utterances (Asriyanti et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows a deep understanding of the concept of using technology. Teachers should be able to communicate effectively, using clear and comprehensible language to positively influence students' perceptions (Yulianti et al, 2022;Hasjim et al, 2020;. It is an attempt to avoid multiple interpretations of using difficult dictions and utterances (Asriyanti et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the contemporary era of Society 5.0, individuals are expected to seamlessly integrate virtual and physical spaces to complete their work following established standards efficiently. Furthermore, this digital age is characterized by the availability of diverse information sources (Hasjim et al, 2020;. The pervasive influence of this new era is specifically essential, with the younger generation significantly contributing to its advancement .…”
Section: Introductionmentioning
confidence: 99%
“…It is a practical moral message that readers can interpret throughout the novel. Interpretation can be made in various ways depending on the meaning the readers understand (Hasjim et al, 2020). Argues might emerge among the readers due to these different perceptions .…”
Section: Character Education Valuesmentioning
confidence: 99%
“…In this case, repeating reading several times, notably by voice, ameliorates the students' Speaking Skills and enriches vocabulary mastery. However, (Dhuli et al, 2023) ix found the technique of Reading Aloud has no meaningful effect on students' vocabulary learning (Dhuli et al, 2023 x ;Arafah et al, 2023 xi ), Reading Aloud, if it is frequently undertaken, is a speaking practice and beneficial to vocabulary learning. This activity is significant as an effort to familiarize the pronunciation of English words.…”
Section: Exploring the Importance Of The Problemmentioning
confidence: 99%